Latitude dependence of geomagnetic paleosecular variation and its relation to the frequency of magnetic reversals : Observations from the Cretaceous and Jurassic - Doubrovine, Pavel V.; Veikkolainen, Toni; Pesonen, Lauri J.; Piispa, Elisa; Ots, Siim; Smirnov, Aleksey V.; Kulakov, Evgeniy V.; Biggin, Andrew J. (Geochemistry, Geophysics, Geosystems, 2020)
Nearly three decades ago paleomagnetists suggested that there existed a clear link between latitude dependence of geomagnetic paleosecular variation (PSV) and reversal frequency. Here we compare the latitude behavior of PSV for the Cretaceous Normal Superchron (CNS, 84‐126 Ma, stable normal polarity) and the preceding Early Cretaceous‐Jurassic interval (pre‐CNS, 126‐198 Ma, average reversal rate of ~4.6 Myr‐1). We find that the CNS was characterized by a strong increase in the angular dispersion of virtual geomagnetic poles (VGPs) with latitude, which is consistent with the results of earlier studies, whereas the VGP dispersion for the pre‐CNS period was nearly invariant with latitude. However, the PSV behavior for the last 5 or 10 million years (average reversal frequency of ~4.4‐4.8 Myr‐1) shows that the latitude invariance of VGP scatter cannot be considered as a characteristic feature of a frequently‐reversing field, and that a strong increase in VGP dispersion with latitude was not restricted to the long periods of stable polarity. We discuss models describing the latitude dependence of PSV and show that their parameters are not reliable proxies for reversal frequency and should not be used to make inferences about the geomagnetic field stability. During the pre‐CNS interval, the geodynamo may have operated in a regime characterized by a high degree of equatorial symmetry. In contrast, more asymmetric geodynamos suggested for 0‐10 Ma and the CNS were evidently capable of producing a very wide range of reversal frequencies. Nearly three decades ago paleomagnetists suggested that there existed a clear link between latitude dependence of geomagnetic paleosecular variation (PSV) and reversal frequency. Here we compare the latitude behavior of PSV for the Cretaceous Normal Superchron (CNS, 84–126 Ma, stable normal polarity) and the preceding Early Cretaceous‐Jurassic interval (pre‐CNS, 126–198 Ma, average reversal rate of ~4.6 Myr−1). We find that the CNS was characterized by a strong increase in the angular ...